Phytohormones Signaling Pathways and ROS Involvement in Seed Germination - Oracz, Krystyna; Karpiński, Stanisław (Frontiers in Plant Science, 2016)
Phytohormones and reactive oxygen species (ROS) are major determinants of the regulation of development and stress responses in plants. During life cycle of these organisms, signaling networks of plant growth regulators and ROS interact in order to render an appropriate developmental and environmental response. In plant’s photosynthetic (e.g. leaves) and non-photosynthetic (e.g. seeds) tissues, enhanced and suboptimal ROS production is usually associated with stress, which in extreme cases can be lethal to cells, a whole organ or even an organism. However, controlled production of ROS is appreciated for cellular signaling. Despite the current progress that has been made in plant biology and increasing number of findings that have revealed roles of ROS and hormonal signaling in germination, some questions still arise, e.g. what are the downstream protein targets modified by ROS enabling stimulus-specific cellular responses of the seed? Or which molecular regulators allow ROS/phytohormones interactions and what is their function in seed life? In this particular review the role of some transcription factors, kinases and phosphatases is discussed, especially those which usually known to be involved in ROS and hormonal signal transduction under stress in plants, may also play a role in the regulation of processes occurring in seeds. The summarized recent findings regarding particular ROS- and phytohormones-related regulatory proteins, as well as their integration, allowed to propose a novel, possible model of action of LESION SIMULATING DISEASE 1 (LSD1), ENHANCED DISEASE SUSCEPTIBILITY 1 (EDS1) and PHYTOALEXIN DEFICIENT 4 (PAD4) functioning during seeds life.